Manajemen Mutu Pembelajaran dalam Rangka Optimalisasi Profesionalisme Tenaga Pendidik Di Madrasah/Sekolah - Radiana, Usman; Tursina, Nani; Rudiansyah, Rudiansyah (Ngaji: Jurnal Pendidikan Islam, 2022)
The learning process that occurs in the classroom so far still has many deficiencies that must and need to be addressed in the framework of improvement through quality. Educators are one of the most important factors in the success or failure of the educational goals that have been wanted to be achieved. The success of education lies in the competencies that must be mastered by teachers, one of which is professional competence. Teacher quality also needs to be continuously improved through various teacher professional development programs as a form of effort to improve the quality of learning which has so far not been optimal enough. In this study, researchers used library research which used library sources including literature books, e-book scientific journal articles, and report notes which included undergraduate theses, theses, dissertations, and other relevant documents. Learning quality management is very important to make learning quality/quality in optimizing the professionalism of education staff in schools/madrasas. As a group of professional educational staff, they can be optimized through several components such as planning the quality of learning and implementing the quality of learning to evaluation. In Islam, the attitude of professionalism has been found through His words, and His words as the people must be able to emulate what has been implemented by the Prophet Muhammad SAW. Thus, it can also be a solution to solve educational problems in this era.   Abstrak: Proses pembelajaran yang terjadi didalam kelas selama ini masih banyak kekurangan yang harus dan perlu dibenahi dalam rangka penyempurnaan melalui mutu. Tenaga pendidik menjadi salah satu faktor terpenting berhasil atau tidaknya tujuan pendidikan yang selama ini ingin diraih. Keberhasilan pendidikan terletak pada kompetensi yang harus dikuasai guru salah satunya kompetensi profesionalisme. Kualitas guru juga perlu dibenahi berkelanjutan melalui berbagai program pengembangan keprofesionalisme keguruan sebagai bentuk upaya meningkatkan mutu pembelajaran yang selama ini belum cukup optimal. penelitian ini peneliti menggunakan penelitian pustaka (library research) yang menggunakan sumber kepustakaan meliputi buku literatur, artikel jurnal ilmiah ebook, catatan laporan yang meliputi skripsi, tesis, disertasi serta dokumen lain yang relevan. Manajemen mutu pembelajaran sangat penting untuk menjadikan pembelajaran bermutu/berkualitas dalam optimalisasi keprofesionalisme tenaga kependidikan di sekolah/madrasah. Sebagai tenaga kependidikan keprofesionalannya dapat dioptimalkan melalui beberapa komponen seperti perencanaan mutu pembelajaran, pelaksanaan mutu pembelajaran hingga evaluasi. Dalam Islam sikap keprofesionalan sudah ditemukan melalui firman-Nya maupun sabda-Nya sebagai umatnya harus dapat meneladani yang sudah diimplementasikan oleh Nabi Muhammad SAW. Dengan demikian, dapat juga menjadi solusi untuk memecahkan masalah-masalah pendidikan di era ini. Kata Kunci: Manajemen, Mutu, Pembelajaran, Profesionalisme